Urine-Derived Stem Cells for Epithelial Tissues Reconstruction and Wound Healing - Xiya Yin; Qingfeng Li; Patrick Michael McNutt; Yuanyuan Zhang (MDPI AG, 2022)
Epithelial tissue injury can occur on any surface site of the body, particularly in the skin or urethral mucosa tissue, due to trauma, infection, inflammation, and toxic compounds. Both internal and external body epithelial tissue injuries can significantly affect patients' quality of life, increase healthcare spending, and increase the global economic burden. Transplantation of epithelial tissue grafts is an effective treatment strategy in clinical settings. Autologous bio-engineered epithelia are common clinical skin substitutes that have the specific advantages of avoiding tissue rejection, obviating ethical concerns, reducing the risk of infection, and decreasing scarring compared to donor grafts. However, epithelial cells are often obtained from the individual's skin and mucosa through invasive methods, which cause further injury or damage. Urine-derived stem cells (USC) of kidney origin, obtained via non-invasive acquisition, possess high stemness properties, self-renewal ability, trophic effects, multipotent differentiation potential, and immunomodulatory ability. These cells show versatile potential for tissue regeneration, with extensive evidence supporting their use in the repair of epidermal and urothelial injuries. We discuss the collection, isolation, culture, characterization, and differentiation of USC. We also discuss the use of USC for cellular therapies as well as the administration of USC-derived paracrine factors for epidermal and urothelial tissue repair. Specifically, we will discuss 3D constructions involving multiple types of USC-loaded hydrogels and USC-seeded scaffolds for use in cosmetic production testing, drug development, and disease modeling. In conclusion, urine-derived stem cells are a readily accessible autologous stem cell source well-suited for developing personalized medical treatments in epithelial tissue regeneration and drug testing.